The Analysis of Errors in Translation of Scientific Text from English to Indonesian Language - Mardin Silalahi; Zainal Rafli; Yumna Rasyid (JETL (Journal of Education, Teaching and Learning), 2018)
This study aims to find errors in the translation of scientific texts from English into Indonesian. This research uses the qualitative method with content analysis approach. The results showed that (1) the translation strategy, the majority of students used semantic strategy, especially modulation in translating scientific texts and at least used the special structural strategies of addition, (2) lexical error, the majority of students made formal lexical errors in word selection and the least (3) morphological errors, the majority of students make mistakes in the affixation field of improper use of affixation and the least of which are affixations that are not broken, (4) syntactic errors, syntactical errors found in the translation of scientific texts in the fields, phrases, clauses and sentences but the majority of students make mistakes in the field of sentences are the use of illogical phrases and the fewest errors in the field clause is the addition of auxiliary verbs in the equational or nominal clause, and the separation of the perpetrator (subject) and the word in the active clause, (5) the factor causing errors in translation ie the majority of students do not understand the source language text and the least of which is the quality of the source language using the incorrect grammatical, the sentence is vague, the idea is not coherent and many fungtuations.